Strategic Model for Enhancing the Quality of Islamic Education in the Context of Contemporary Globalization - La Ode Amir Ifan; Moh. Ali; Jamali Jamali; Wasalmi Wasalmi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study examines strategic approaches to enhancing the quality of Islamic education within the dynamic landscape of contemporary globalization. Accelerated technological innovation, intensified cultural interaction, and increasing global competition have significantly reshaped educational systems worldwide. Consequently, Islamic educational institutions are challenged to modernize their structures and practices while preserving their theological foundations and moral commitments. This research applies a qualitative library-based methodology, drawing upon contemporary educational theories, Islamic pedagogical traditions, and policy frameworks on quality assurance and institutional development. The findings reveal that improving educational quality in Islamic institutions requires a multidimensional strategy. Key dimensions include curriculum transformation aligned with global standards, continuous professional development for teachers, effective digital integration, transparent and accountable governance, and character education grounded in Islamic ethical values. Strengthening visionary leadership, implementing outcome-based education models, and fostering integration between religious sciences and modern disciplines are essential to achieving global competitiveness. Moreover, Islamic education must cultivate critical thinking, intellectual openness, moderation (wasatiyyah), intercultural dialogue, and ethical responsibility to respond constructively to globalization. Sustainable quality enhancement depends on stakeholder collaboration, pedagogical innovation, and systematic evaluation. By harmonizing spiritual depth with academic rigor, Islamic education can remain relevant, adaptive, and transformative in preparing morally grounded and globally competent generations